Trickling Down or Fizzling Out? Economic Performance, Transfers, Inequality, and Low Income in Canada - Zyblock, Myles; Lin, Zhengxi (Journal of Income Distribution®, 2000)
This paper examines the empirical relationships between economic performance, transfers, and low income among Canadian families, and explores whether these relationships have changed over time. Similar recent studies in the U.S. find a weakening in the negative relationship between economic growth and low income over the past 25 years. Using data extracted from the Canadian Survey of Consumer Finances (SCF), we find that improving economic performance reduces the incidence of low income among families in Canada from 1973 to 1995. Government transfers are also found to lift families above the low-income threshold. These results are robust across different family types and for three different measures of low income. {Copyright 2001 Elsevier Science Inc. All rights reserved}.